Potassium channel‐mediated NO‐induced vasodilation during maturation: Dominance of Kv7 channels - Anastasia A. Shvetsova; Dina K. Gaynullina; Peter Winkler; Paulus Wohlfart; Rudolf Schubert (FASEB BioAdvances)
Abstract Maturation represents a process characterized by adaptive changes, particularly in the circulatory system. However, it is not known whether, in neonates, potassium channels contribute to NO‐induced vasorelaxation at all and, if so, which potassium channels these are. Therefore, this study tested the hypothesis that potassium channels mediate NO‐induced vasorelaxation in newborn rats. Young (10‐ to 15‐day‐old) and adult (2‐ to 3‐month‐old) male rats were studied using real‐time PCR, isometric myography, and the sharp microelectrode technique on saphenous arteries. We observed prominent mRNA expression of several distinct isoforms of potassium channel families known to potentially mediate SNP‐induced vasodilation. Further, in both adult and young rats, SNP can relax vessels independently of potassium channels. A solely potassium channel‐independent anticontractile effect of SNP was observed also when either Kir6, or Kir2, or Kv2 channels, respectively, were available in both adult and young rats. However, when Kv1 channels were available, a Kv1 channel‐dependent component contributed to the anticontractile effect of SNP in young rats. When BKCa channels were available, a BKCa channel‐dependent component contributed to the anticontractile effect of SNP in adult rats. A considerable Kv7 channel‐dependent component contributed to the anticontractile effect of SNP in both adult and young rats. Thus, the data of the present study show for the first time that potassium channels, even multiple ones, contribute to SNP‐induced vasorelaxation in newborn rats and that the potassium channels involved in SNP‐induced vasorelaxation change from Kv1/Kv7 channels to BKCa/Kv7 channels during postnatal development.